Impact of the Reduction Time-Dependent Electrical Conductivity of Graphene Nanoplatelet-Coated Aligned Bombyx mori Silk Scaffolds on Electrically Stimulated Axonal Growth - Monaghan, Michael; Borah, Rajiv (My University, 2024)
Graphene-based nanomaterials, renowned for their outstanding electrical conductivity, have been extensively studied as electroconductive biomaterials (ECBs) for electrically stimulated tissue regeneration. However, using eco-friendly reducing agents like l-ascorbic acid (l-Aa) can result in lower conductive properties in these ECBs, limiting their full potential for smooth charge transfer in living tissues. Moreover, creating a flexible biomaterial scaffold using these materials that accurately mimics a specific tissue microarchitecture, such as nerves, poses additional challenges. To address these issues, this study developed a microfibrous scaffold of Bombyx mori (Bm) silk fibroin uniformly coated with graphene nanoplatelets (GNPs) through a vacuum coating method. The scaffold’s electrical conductivity was optimized by varying the reduction period using l-Aa. The research systematically investigated how different reduction periods impact scaffold properties, focusing on electrical conductivity and its significance on electrically stimulated axonal growth in PC12 cells. Results showed that a 48 h reduction significantly increased surface electrical conductivity by 100–1000 times compared to a shorter or no reduction process. l-Aa contributed to stabilizing the reduced GNPs, demonstrated by a slow degradation profile and sustained conductivity even after 60 days in a proteolytic environment. β (III) tubulin immunostaining of PC12 cells on varied silk:GNP scaffolds under pulsed electrical stimulation (ES, 50 Hz frequency, 1 ms pulse width, and amplitudes of 100 and 300 mV/cm) demonstrates accelerated axonal growth on scaffolds exhibiting higher conductivity. This is supported by upregulated intracellular Ca2+ dynamics immediately after ES on the scaffolds with higher conductivity, subjected to a prolonged reduction period. The study showcases a sustainable reduction approach using l-Aa in combination with natural Bm silk fibroin to create a highly conductive, mechanically robust, and stable silk:GNP-based aligned fibrous scaffold. These scaffolds hold promise for functional regeneration in electrically excitable tissues such as nerves, cardiac tissue, and muscles.
PUBLISHED
https://doi.org/10.1021/acsabm.4c00052
Keywords: silk; graphene; electroconductive biomaterials; electrical stimulation; nerve regeneration; Neuroscience; Next Generation Medical Devices